Spatial and seasonal characteristics of dissolved heavy metals in the seawater of Beibu Gulf, the Northern South China Sea - Zhu, Zuhao; Wei, Huihua; Guan, Yao; Zhang, Li; Sun, Pengfei; Zhang, Qiufeng (Frontiers in Marine Science, 2022)
Heavy metal contaminations in the marine environment are of considerable attention because of their high potential ecological effects and public concern for human health. However, the influencing factors for the large-scale distributions of heavy metals in Beibu Gulf, a newly developing industry and port in South China, are still unclear due to the lack of large-scale investigation. Here, a total of 871 samples in the 127 stations in the seawater of Beibu Gulf during spring, summer, fall and winter in 2020-2021 were analyzed for dissolved heavy metal concentrations and physicochemical parameters. The concentrations of heavy metals in the Beibu Gulf ranked following the order of Zn > Cu > Cr > As > Pb > Hg > Cd. Compared to other regions, the concentrations of Hg were at relatively higher levels, which were mainly influenced by the input of the transportation of water masses from the local and other regions; whereas the other heavy metals were at relatively lower levels. Seasonally variations in the concentrations of heavy metals were observed in the gulf, which is mainly influenced by human activities (i.e., shipping and mariculture activities) and seasonally hydrological conditions. Seasonal changes in the spatial distribution of heavy metals have been found in the gulf. The higher concentrations of heavy metals mainly occurred in the coastal bays or areas in summer whereas the higher concentrations were observed in the offshore areas during the other three seasons. This is mainly related to the seasonal changes of the water masses that affect the seawater of Beibu Gulf, which exhibits the dominant contribution of coastal current from the northern Beibu Gulf in summer, and the dominant contribution of west-Guangdong coastal current and SCS water during the other three seasons. The potential ecological risk index revealed that Hg is the main ecological risk factor in the gulf, and the heavy metal contamination in the gulf seems to be noticeable. This study highlights the seasonal changes of the water masses that affect the seawater of Beibu Gulf greatly affecting the large-scale distributions of heavy metals in the gulf.